Land, Culture and Community: Envisioning Native American Sovereignty and National Identity in the 21st Century - Tsosie, Rebecca (Hagar: Studies in Society and Culture, 2001)
This article focuses on three important elements of Native American sovereignty and national identity as these concepts relate to tribal lands. First of all, it examines the notion of territorial sovereignty for Indian nations, and how federal policy toward Indian lands has changed the nature and understanding of political sovereignty among Indian nations. Secondly, it examines the notion of ‘cultural sovereignty’ and the land ethics that guide the actions of Indian nations toward their traditional lands. Finally, it examines the idea of ‘community’ broadly construed to encompass the people who reside on the reservation, and snore narrowly construed to reflect the tribe’s own cultural understanding of its membership. The paper compares federal policy with tribal policy to see where the disjunctions are, and how a more unified understanding of these essential concepts might be used to further the contemporary goals and needs of Indian nations.